Gender and Racial Stereotypes in Popular Video Games - Mou, Yi; Peng, Wei (Handbook of Research on Effective Electronic Gaming in Education, 2009)
While the violent content of video games has caused wide concern among scholars, gender, and racial stereotypes in video games are still an understudied area. The purpose of this chapter is to provide a better understanding of the stereotypical phenomenon in video games. The book chapter first provides a comprehensive review of previous studies conducted upon gender-role and racial portrayals in video games. Then a small-scale content analysis on a sample of official trailers, introductory sequences and covers of 19 of the most popular video games is introduced. Finally, the implications of stereotype in video games and the possible social and psychological impacts on players, especially adolescent players, are discussed.
Keywords: 1-Jeux vidéo; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude de la réception; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; _Nettoyé